MapTalk: mosaicking physical objects into the cyber world. Issue 3 (3rd July 2018) - Lin, Yi-Bing; Shieh, Min-Zheng; Lin, Yun-Wei; Chen, Hsin-Ya
ABSTRACT: Digital map is considered as a cyber world, which maps visual representations (cyber objects) to the physical objects in the real world and allows the user to interact with these physical objects through their cyber representations. However, it typically requires significant programming effort to create a map application. This paper proposes MapTalk, a web-based visual map platform that allows the user to interact with the physical objects through their cyber representations in a visual map. We show how the administrator can add applications to the map without any programming effort. The novel idea in our approach is to utilise the IoT concept. Specifically, we implement the map as an output IoT device and all physical objects to be mosaicked in the map as input IoT devices. We show how to automatically create the device features of IoT devices when the administrator creates applications in the Map web page. We have deployed over 20 services in MapTalk including smart home, smart farm, tracking (bus, person, dog, etc), video monitoring, travel route planning, sensing of CO2, PM2.5, Internet of Things (IoT). temperature, humidity, and so on. Abbreviation : Internet of Things (IoT)